Swyer–James–MacLeod syndrome—a rare diagnosis presented through two adult patients. Issue 5 (16th June 2017) - Mehra, Sumit; Basnayake, Thilini; Falhammar, Henrik; Heraganahally, Subash; Tripathi, Suryakant
Abstract : Swyer–James–MacLeod syndrome (SJMS) is a rare syndrome of acute obliterative bronchiolitis following an early childhood infective insult to the lungs. This causes arrest of alveolarization, affecting lung development with hypoplasia of the ipsilateral pulmonary artery and results in a characteristic radiological pattern, such as a unilateral hyperlucent lung with expiratory air‐trapping and pruned‐tree appearance on pulmonary angiogram. The clinical presentation is either recurrent chest infections, exertional dyspnoea or it may be an incidental finding. Management involves early prevention of infection, airway clearance, and regular vaccinations. We describe two adult patients with SJMS: A 51‐year‐old female of Indian ethnicity presenting with recurrent haemoptysis and a 40‐year‐old Indigenous male presenting acutely with sepsis and background history of recurrent chest infections. These cases highlight the importance of being aware of and accurately recognizing this rare condition, to be able to manage patients appropriately and avoid incorrect and unnecessary treatment. Abstract : Swyer–James–MacLeod syndrome (SJMS) is a rare disorder that manifests as unilateral hyperlucent lung with expiratory air‐trapping and is a result of post‐infectious acute obliterative bronchiolitis. It is often misdiagnosed. It is important to recognize the condition to achieve better prognosis and also to prevent inappropriate treatment.